(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2018)
The lexical lists that can be found in the avantext of the Proposta di alcune correzioni ed aggiunte al Vocabolario della Crusca (1817-1826) by Vincenzo Monti allow to highlight some of the mechanisms which set the making of the poet’s lexicographic and linguistic thought from an unprecedented point of view.